Evaluasi Kebijakan Program BPJS Gratis Di Kota Bengkulu - Sianturi, Mega Wati; Saputra, Harius Eko; Yusuarsono, Yusuarsono; Lorita, Evi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This research aims to find out Policy Evaluation of Free BPJS Program in Bengkulu City. Data collection techniques are carried out by means of observation, interviews and documentation. Data analysis techniques by means of data reduction, data presentation and drawing conclusion. The informants in this study amounted to 10 people consisting of 4 key informants and 6 main informants. The theory used in this research is the theory of evaluation models according to Wayne Parsons (in Yessi Utari 2021: 30). There are two types of policy evaluation models used, namely Formative Evaluation and Summative Evaluation. Based on the research results, conclusions can be drawn, namely: 1. Formative Evaluation: a. The purpose of this free BPJS program is to prosper the people of Bengkulu city in the health sector. b. Background of Free BPJS Policy, this free BPJS program is based on Mayor Regulation no.14 of 2022. c. Free BPJS Policy Formulated in Bengkulu City, this policy is a mandate from the 1945 Constitution and the Indonesian Law No.17 of 2023 concerning health. d. The funding allocated for Free BPJS Program is from APBD funds taken from the cigarette tax based on the Indonesian Minister of Finance Regulation no.128/PMK.07/2018 and Governor Regulation no.11 of 2017. e. Implementation of Free BPJS Program Policy in Bengkulu City, this free BPJS policy has provisions, namely Identity Card and Family Card who are domiciled in Bengkulu City, as well as Certificate of Indigence from Urban Village. f. The Relevance of Free BPJS Program among the People of Bengkulu City is still less relevant, especially in terms of service at health facilities when seeking treatment, it is still a little slow in health consultations or taking medicine. g. The service quality is quite good and very helpful. The service quality is quite good and very helpful to the community. h. The problem felt is the sudden deactivation of membership and the registration of online services for parents who are difficult to understand. i. Free BPJS program should improve facilities and services at the first health facility. 2. Summative Evaluation: a. This program helps the community in the health sector. b. The success of free BPJS program has been quite successful because many people in Bengkulu City have been helped. c. This Free BPJS has helped the community to seek treatment. d. The obstacles or challenges felt are the system of free BPJS program. The obstacles or challenges felt are the application system and people who transfer their residence. e. The budget evaluation is felt to be right on target but for the evaluation of human resources it is determined by credentials..